Pro SQL Server 2008 Analysis Services - Janus, Philo (Apress, 2012)
Pro SQL Server 2008 Analysis Services offers an in-depth look into the latest and greatest suite of analytic tools from Microsoft. This book will help you create business intelligence (BI) solutions that improve your company’s analysis and decision making by focusing on practical, solution-oriented application of the technologies available in SQL Server 2008 Analysis Services (SSAS).